Utilization of Wood Industry Waste as Raw Material for Cement Boards Production - Azhari Azman1Sushardi, Mohamed Nor (International Journal of Advanced Science and Technology, 2020)
The technology of cement board should be developed by using the wood industry waste especially in the form of lignocellulose since it is a good material and could give a lot of benefit towards the humankind. It can bring a great impact which to cut down the enormous expense and can generate a higher economic value. Therefore this research aims to study the influence of waste particle treatment and the level of cement adhesive to produce cement board which is made from the wood industry waste. This research is based on factorial experiment by using a completely random design for Tukey test. It consists of the treatment of waste particle (without soaking, soak in cold water and hot water) and the proportion of cement adhesive with (150%, 200% and 250% from the weight of the substance). The parameters to observe are water content, density, modulus of rupture, modulus of elasticity and reduction of thickness with pressure of 3kg/cm2. The result shows that the treatment of waste particle and the proportion of cement produce an obvious influence to the nature physics and the production of cement boards. The nature of physics and the property of cement board from the wood industry waste has meet the standard of DIN 1101.